A mini review of giant invasive sacral schwannoma - Hannah H. Chen; Eugene Tikh; Gord G. Zhu (Elsevier, 2022)
Primary giant invasive sacral schwannoma is a rare disease. Its uncommon location and aggressive growth behavior with eroding bone and compressing adjacent structures may lead to misdiagnosis. Awareness of this rare entity will help pathologists to differentiate it from other tumors possibly seen at this location. In this review, we summarize its clinical features, histopathology, differential diagnoses, treatment, and prognosis.